Flexural performance of innovative sustainable composite steel-concrete beams. (1st January 2017) - Liu, Xinpei; Bradford, Mark A.; Ataei, Abdolreza
Highlights: Proposes new composite beam with high-level sustainability attributes. First use of a composite beam with a precast geopolymer slab. FE modelling is developed and invoked to assess the structural feasibility of the beam. Deconstructability of the novel beam is achieved using high-strength friction-grip bolted shear connectors. Tests and FE model confirm highly ductile and more favourable strength than conventional composite beams. Abstract: Composite beams comprising of concrete slabs and steel beams joined by conventional headed stud shear connectors are commonly used in modern steel-framed building construction. However, because the headed stud shear connectors are welded onto the top flange of the steel beam and cast into the in situ concrete slab, deconstruction of the composite beam and the reuse of its components at the end of structural life in defence to demolition is virtually impossible, which is at odds with the increasing demands placed on improving the sustainability of building infrastructure. As an alternative, an innovative sustainable composite beam and slab system is proposed, in which precast geopolymer concrete panels are attached to the steel beams using high-strength friction-grip bolts instead of cast in situ floors with pre-welded headed stud connectors. The advantages of a low-carbon design, both by the use of geopolymer concrete elements and system deconstructability, can be achieved in this proposed system. In this paper, a three-dimensional finite element model is developed to investigate the structural behaviour of the proposed sustainable composite beam and slab system. Material non-linearities and the interaction of the structural components are included in the model. The accuracy and reliability of the finite element formulation developed are validated by comparisons with experimental results. Extensive parametric studies are conducted to elucidate the effects of the change in the concrete panel configuration, the number and diameter of the bolts, the type and strength of the concrete and the grade of the steel beam on the behaviour of the system. The use of modified rigid plastic analysis is assessed, and a modification is suggested to predict the flexural strengths of the composite beams and slab system.